Impact of Service Quality on In-Patients’ Satisfaction, Perceived Value, and Customer Loyalty: A Mixed-Methods Study from a Developing Country - Nguyen NX; Tran K; Nguyen TA (Patient Preference and Adherence, 2021)
Nhi Xuan Nguyen,1 Khoa Tran,1 Tuyet Anh Nguyen2 1Faculty of Business Administration, Nguyen Tat Thanh University, Ho Chi Minh City, Vietnam; 2Department of Business, Minerva University, San Francisco, CA, USACorrespondence: Khoa TranFaculty of Business Administration, Nguyen Tat Thanh University, 300A Nguyen Tat Thanh, Ward 13, District 4, Ho Chi Minh City, VietnamTel +84 562 688 998Email anhkhoatran3007@gmail.comPurpose: Recent literature on healthcare quality demands more contextualized and patient-perspective research, as models from developed countries are not suitable for developing countries. Moreover, research on private healthcare services in Vietnam has long been underestimated by academia, but it has significant economic and commercial value. Hence, this study explores the dimensions of service quality in private healthcare and how they impact in-patient satisfaction, perceived value, and customer loyalty in Vietnam.Methods: This mixed-method study had a sample size of five inpatients for the qualitative phase and 368 inpatients for the quantitative phase from hospitals in Vietnam. The qualitative analysis explores service quality dimensions in private healthcare and incorporates them with the literature to develop a conceptual model. The quantitative phase tests the relationship between each construct in the conceptual model via structural equation modeling.Results: The four dimensions of service quality were emotion, function, social influence, and trust. Most of these dimensions have a significant impact on customer perceived value and satisfaction. However, emotion does not significantly influence customer perceived value, and function does not considerably impact customer satisfaction. In addition, social influence is an underrepresented variable in the service quality literature, but it has the most substantial impact on customer perceived value and customer satisfaction. The quantitative results also confirm that customer satisfaction and customer perceived value significantly impact customer loyalty (word-of-mouth and revisit intention); however, customer perceived value does not significantly impact customer satisfaction.Conclusion: The study suggests that private healthcare providers and the government in Vietnam should allocate resources to improve service quality. Practitioners should invest in social branding and e-services to reach out to their customers. Future research should focus on a cost-benefit analysis and compare the effectiveness of service quality dimensions on customer behavioral intention.Keywords: customer perceived value, customer satisfaction, private healthcare, revisit intention, service quality, word-of-mouth